(untitled) (City: History, Culture, Society, 2023)
The article analyses the approaches to assessing the quality of drinking water that was used in the provincial city of Poltava in the 19th and early 20th centuries. It traces the evolution from drinking water quality organoleptic approaches (which rely on human senses and subjective perception) to more advanced and objective methods like chemical and bacteriological analyses. Besides, the paper examines various factors that could affect the quality of water in the city, primarily anthropogenic pressure (episodic and temporary population growth), lack of environmental awareness, non-compliance with sanitary standards, and the objective inability to meet government sanitary requirements. The study also delves into efforts to provide safe drinking water to the city’s inhabitants. It investigates both the positive and negative outcomes of introducing a centralized water supply system (without a corresponding sewage system). Additional attention is paid to the policies of urban institutions that require water supply under their activities. The article also addresses the problems of unequal access to drinking water for different segments of the population and social groups, as well as the connection between water quality and the typhoid and cholera epidemics that took place in this historical period. The results of anti-epidemic measures aimed at improving the city’s water supply during the 1892 and 1907–1910 cholera epidemics are analysed. The article concludes that improving the quality of life, including through water supply, should not be seen as a continuous movement forward and "evolution". For a nineteenth-century Ukrainian provincial city, anthropogenic factors derived from the city’s provincial status could have a stronger (negative) impact on water quality than the sanitary measures of the local administration and doctors. Changes in water supply varied among different social groups and city districts, giving rise to disparities and inequalities that merit further investigation.